Pengaruh Sikap Keuangan dan Status Sosial terhadap Literasi Keuangan Siswa SMA Kesehatan 2 Tambrauw - Sapari, Lili Sarce Joi; Timisela, Yanti; Sirawi, Yunita Lisbeth (Innovative: Journal Of Social Science Research, 2024)
The aim of this research is to determine the influence of financial attitudes and social status on the financial literacy of students at SMK Kesehatan 2 Tambrauw. The analysis technique used is multiple linear regression. Research results: The results of multiple linear regression carried out using SPSS 25, the linear regression equation formed is: ???? = 7.222 + 0.103????1 + 0.008????2 + ????; Financial Attitude Variable; Based on the table above, testing the hypothesis of the influence of financial attitudes on financial literacy obtained a significance level of 0.003 with a calculated t value > t table of 2,540 > 1.681 and a significance value smaller than 5% (0.05) or (0.003 > 0.05). So the hypothesis that financial attitudes influence financial literacy, where Ha is accepted and Ho is rejected; Testing the hypothesis of social status on financial literacy obtained a significance level of 0.020 with a calculated t value > t table of 2,063 > 1.681 and a significance value smaller than 5% (0.05) or (0.020 < 0.05). So the hypothesis that social status influences financial literacy, where Ha is accepted and Ho is rejected.